Optimization and cutting‐edge design of fuel‐cell hybrid electric vehicles. (31st July 2021) - Luo, Yang; Wu, Yinghong; Li, Bo; Qu, Jingkui; Feng, Shien‐Ping; Chu, Paul K.
Summary: The transportation sector consumes a large amount of fossil fuels consequently exacerbating the global environmental and energy crisis. Fuel‐cell hybrid electric vehicles (FCHEVs) are promising alternatives in the continuous transition to clean energy. This article summarizes the recent advances pertaining to the optimization and cutting‐edge design of fuel‐cell hybrid electric vehicles, especially the fuel cell + battery hybrid topology, and discusses current technological bottlenecks hindering the commercialization of FCHEVs. The development of HEVs, markets, environmental and economic benefits, components, topologies, energy management strategies, degradation mechanisms, and safety standards of FCHEVs are reviewed. Proton exchange membrane fuel cells constitute the mainstream and most mature fuel cell technology for automobile applications. Battery hybridization is currently favored among the available FCHEV topological designs to improve the dynamic response and recover the braking energy. Energy management strategies encompassing logic rule‐based simple methods, intelligent control methods, global optimization strategies, and local optimization strategies are described, and issues and challenges encountering FCHEVs are discussed. In addition to promoting the construction of hydrogen supply facilities, future efforts are expected to focus on solving problems such as the high cost, durability of fuel cells, cold start, lifetime of batteries, security and comfort, system optimization, energy management systems, integration, and diagnosis of faults. This review serves as a reference and guide for future technological development and commercialization of FCHEVs. Highlights: Advances of the optimization and cutting‐edge design of FCHEVs are reviewed. Battery hybridization is currently favored among the available topological designs. Benefits, components, topologies, and energy management strategies are described. Markets, degradation mechanisms, and safety standards of FCHEVs are introduced. Technological bottlenecks hindering the commercialization of FCHEVs are discussed. Abstract : This article summarizes the recent advances pertaining to the optimization and cutting‐edge design of fuel‐cell hybrid electric vehicles, especially the fuel cell + battery hybrid topology, and discusses current technological bottlenecks hindering the commercialization of FCHEVs. Energy management strategies encompassing logic rule‐based simple methods, intelligent control methods, global optimization strategies, and local optimization strategies are described, and issues and challenges encountering FCHEVs are discussed. This review serves as a reference and guide for future technological development and commercialization of FCHEVs.